2012
DOI: 10.1007/s00261-012-9911-5
|View full text |Cite
|
Sign up to set email alerts
|

Epithelioid angiomyolipoma of the liver: CT and MRI features

Abstract: The purpose of our study was to retrospectively evaluate the computed tomography (CT)/magnetic resonance imaging features of epithelioid angiomyolipoma of the liver (Epi-HAML), with pathology as a reference. We reviewed the CT/MRI findings of six lesions of Epi-HAML and found absence of adipose tissue in the lesions. In addition, recognizing the imaging features of no capsule, and hypervasularity with central punctiform or filiform vessels as a characteristic enhancement may distinguish Epi-HAML from other hep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 13 publications
2
47
2
1
Order By: Relevance
“…Familiarity with the features of hepatic AMLs on clinical imaging could increase the rate of detection and reduce the chance of misdiagnosis. Extensive CT and MRI studies have been performed (Butte et al 2011;Ji et al 2013;Yang et al 2013b;Yu et al 2013) that have documented that CT and MRI, especially with contrast enhancement, are useful tools in the differential diagnosis of hepatic AML before pathologic examination. Although the combination of US, CT and MRI and, occasionally, angiography increases accuracy in diagnosing hepatic AML, the correct pre-operative diagnostic rate of imaging studies has been reported to be less than 50% (Yang et al 2007).…”
Section: Introductionmentioning
confidence: 98%
“…Familiarity with the features of hepatic AMLs on clinical imaging could increase the rate of detection and reduce the chance of misdiagnosis. Extensive CT and MRI studies have been performed (Butte et al 2011;Ji et al 2013;Yang et al 2013b;Yu et al 2013) that have documented that CT and MRI, especially with contrast enhancement, are useful tools in the differential diagnosis of hepatic AML before pathologic examination. Although the combination of US, CT and MRI and, occasionally, angiography increases accuracy in diagnosing hepatic AML, the correct pre-operative diagnostic rate of imaging studies has been reported to be less than 50% (Yang et al 2007).…”
Section: Introductionmentioning
confidence: 98%
“…The preoperative diagnosis of these cases on imaging is very difficult, with a diagnostic accuracy ranging from 0 to 23%. Moreover, the imaging features of this tumour are associated with the histological components; in particular, most tumours were completely devoid of adipose tissue, and hence, fat attenuation was rarely observed on computed tomography and magnetic resonance images . In contrast, nearly all tumours were markedly enhanced in the arterial phase, indicating the presence of a hypervascular tumour .…”
Section: Discussionmentioning
confidence: 94%
“…The radiologic findings were also non-specific, so that misdiagnosis was common before the pathologic diagnosis. Nearly all tumors were well enhanced in arterial phase because of the high vascularity, and some of them showed decreased enhancement at portal and delayed phase [14]. These findings can mimic the typical radiologic findings of hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%